An atypical type A thymoma with lung invasion and pleural metastasis: A case report - Takahide Toyoda; Atsuko Masunaga; Mitsutoshi Shiba; Kenzo Hiroshima (Elsevier, 2017)
Type A thymomas are thymic tumors with low-grade malignant potential that seldom invade adjacent organs. Some of them exhibiting cytological atypia are classified as atypical type A thymomas. A 54-year-old man was referred to our hospital because his chest X-ray examinations showed a lobular anterior mediastinal mass, which was 52 mm in size and had an eggshell-like calcification inside. As preoperative examinations suggested invasive thymoma, tumor extirpation was performed. The histological examination showed an epithelial cell predominant tumor with atypical spindle and polygonal cells invading the lung parenchyma as well as degeneration, necrosis, and bleeding accompanying the eggshell-like calcification. Pleural metastases were also noted. Tumor cells were positive for cytokeratin (CK) AE1/AE3, CAM5.2, CK5/6, but EMA was negative. TdT-positive and CD99-positive T cells were observed in the tumor. Given that the tumor was situated in the anterior mediastinum surrounded by involuted thymus and adipose tissue, we diagnosed this case as an invasive thymoma (T3N0M1a Stage IVA [UICC]; Stage IVA [Masaoka]). Although it was difficult to differentiate type A thymoma from type B3 thymoma based on morphology, we diagnosed this case as atypical type A thymoma because rosette structures and hemangiopericytoma-like patterns were present in the tumor and the tumor was predominantly composed of atypical spindle cells. Moreover, the Ki-67 labeling index was 3% in the main tumor and 10% in metastatic nodules. Immunoprofile of this tumor suggests that the tumor described here is a bridge between common type A thymoma and type B3 thymoma.